MUSIC ANALYSIS ON EBIET G. ADE’S TITIP RINDU BUAT AYAH - Bryan Alvindo Videl Raranta; Perry Rumengan; Meyny Kaunang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This research aims to find out how the meaning of longing in the lyrics of Ebiet G Ade's song entitled Titip Rindu Buat Ayah. The song Titip Rindu Buat Ayah created by Ebiet G Ade and released in 1990 has the meaning of the harshness of life that must be passed by every father as the head of the household who must be responsible for his family in all conditions. The method used is a qualitative method with a musicological approach. Data collection is done by literature review. The song Titip Rindu Buat Ayah is the object is this study. The song lyric is analyzed using Barthes' semiotic theory which consists of denotation, connotation, and myth so that the meaning of loneliness in the song is known. Based on the findings, the meaning contained in the song lyric Titip Rindu Buat Ayah by Ebiet G Ade is the author was so close and longing for the father figure in his life. The author pays so much attention to the father that the author can describe in detail the father's condition. Memories with the father are so imprinted that the author can describe how his father struggles to meet the needs of his family. The longing experienced by the author for the father is so deep but now it is just a meaningless longing.